Investigate channel rectifications and neural dynamics by an electrodiffusive Gauss-Nernst-Planck approach. - Zichao Liu; Yinyun Li (PLoS Computational Biology, 2025)
Electrodiffusion plays a crucial role in modulating ion channel conductivity and neural firing dynamics within the nervous system. However, the relationship among ion electrodiffusion, concentration changes, as well as channel conductivity and neuronal discharge behaviors is not quite clear. In this work, we introduce a novel Gauss-Nernst-Planck (GNP) approach to investigate how electrodiffusive dynamics influence ion channel rectification and neural activity. We have analytically demonstrated how the membrane conductance changes along with voltage and ion concentrations due to the electrodiffusive dynamics, bridging the gap between the permeability-based Goldman-Hodgkin-Katz (GHK) model and conductance-based models. We characterize the rectification properties of [Formula: see text], [Formula: see text] and leaky channels by estimating their single-channel permeabilities and conductance. By integrating these rectifying channels into neurodynamic models, our GNP neurodynamic model reveals how electrodiffusive dynamics fundamentally shape neural firing by modulating membrane conductance and the interplay between passive and active ion transport-mechanisms, which exhibits difference from conventional conductance-based neurodynamic models especially when ion concentration accumulates to high levels. Furthermore, we have explored how the electrodiffusive dynamics influence the pathological neural events by modulating the stability of neurodynamic system. This study provides a fundamental mechanistic understanding of electrodiffusion regulation in neural activity and establishes a robust framework for future research in neurophysiology.